Service-learning in initial teacher training: Analysis of benefits and challenges through a mixed-methods study of three experiences - Martín-Ondarza, Prado; Redondo-Corcobado, Paloma; Gálvez Martín, Beatriz; Fuentes, Juan Luis (International Journal of Research on Service-Learning and Community Engagement, 2026)
Service-learning (S-L) is an educational methodology that links academic training with community service, promoting ethical responsibility, civic engagement, and students’ professional development. This study analyzes the impact of S-L in initial teacher training, focusing on its contribution to curricular, ethical- civic, and professional learning, as well as the development of social competencies. Through the participation of students in three S-L projects at the Complutense University of Madrid, a mixed-methods approach combining qualitative and quantitative analysis is employed. The results show that S-L fosters meaningful and comprehensive learning, highlighting critical reflection as a key element that connects learning, service, and profesional development. They also demonstrate improvements in communication, interpersonal, and ethical-civic skills, as well as a high level of student satisfaction and motivation, with students considering S-L a transformative experience both personally and professionally. In conclusion, its potential to foster methodological innovation and contribute to a more inclusive and equitable education is reaffirmed, forming educators committed to social transformation.
El Aprendizaje-Servicio en la formación inicial del profesorado Análisis de beneficios y desafíos a través de un estudio mixto de tres experiencias
El Aprendizaje-Servicio (ApS) es una metodología educativa que vincula la formación académica con el servicio a la comunidad, promoviendo la responsabilidad ética, el compromiso cívico y el desarrollo profesional del estudiantado. Este estudio analiza el impacto del ApS en la formación inicial del profesorado, centrándose en su contribución al aprendizaje curricular, ético-cívico y profesional, así como al desarrollo de competencias sociales. Tras la participación de 139 estudiantes de tres Grados distintos de la Universidad Complutense de Madrid en tres proyectos de ApS, se empleó una metodología mixta que combina datos y análisis cualitativos y cuantitativos. Los resultados muestran que el ApS favorece un aprendizaje significativo e integral, destacando la reflexión crítica como un elemento clave que conecta el aprendizaje, el servicio y el desarrollo profesional. Asimismo, se evidencian mejoras en las habilidades comunicativas, interpersonales y ético-cívicas, así como un alto nivel de satisfacción y motivación del alumnado, que considera el ApS una experiencia transformadora tanto a nivel personal como profesional. En conclusión, se reafirma el potencial del ApS para fomentar la innovación docente universitaria y contribuir a una educación más inclusiva y equitativa, formando educadores comprometidos con la transformación social.
Keywords: civic engagement; critical reflection; educational innovation; initial teacher training; service-learning; compromiso cívico; reflexión crítica; innovación educativa; formación inicial del profesorado; aprendizaje-servicio